A basic guide to civil litigation in Malaysia - Sufian, Azlinor; Md. Amin@Fahmy, Wan Liza (Global Press, 2010)
This book is aimed to give a basic guidelines to students or any young practitioners who just embarked on the civil litigation practice in court. The book provide step by step procedures and checklists that may be used as guidelines in making application before the court. For instance in making an interloutory application and preparing the case for case management and full trial.